First Complex Allotransplantation of Neck Organs: Larynx, Trachea, Pharynx, Esophagus, Thyroid, Parathyroid Glands, and Anterior Cervical Wall. Issue 2 (August 2017) - Grajek, Maciej; Maciejewski, Adam; Giebel, Sebastian; Krakowczyk, Łukasz; Ulczok, Rafał; Szymczyk, Cezary; Wierzgon, Janusz; Szumniak, Ryszard; Dobrut, Miroslaw; Oleś, Krzysztof; Drozdowski, Piotr; Walczak, Dominik; et al.
Abstract : Objective: Evaluate the possibility of performing a complex vascular allotransplant of all neck organs including skin. Summary Background Data: There are 2 previous attempts described in the literature, none of them being that complex. The first one is nonfunctional due to chronic rejection, the second one is viable yet considerably limited in complexity (no parathyroids, no skin). Methods: The allotransplantation was performed simultaneously on 2 adjacent operating rooms, using microsurgical techniques. Results: The patient's voice, breathing through mouth, swallowing, and endocrinal functions have been fully restored. Conclusions: Achieved results show clearly that such operations performed in selected patients can nearly fully restore functional and aesthetic effects in 1 single procedure.